Psychological And Pedagogical Risks Of Polycultural Education In Armenia - Gevorkyan, Mayranush (Զանգակ հրատ.)
The article examines the features, opportunities and pedagogical risks of polycultural education in the educational environment of Armenia. It is substantiated that the problem of polyculturalism has long gone beyond the scope of its study in the context of a multinational region and is considered from the point of view of a culturological approach. Determining the characteristics and possibilities of polycultural education makes it necessary to take into account the undesirable consequences caused by the existing risks. The main risks of polycultural education are the following: strategic risks, personal risks, psychological risks, communication risks, sociocultural risks.
Keywords: Pedagogy